Perceptions and Motivations to Prevent Heart Disease among Puerto Ricans - Mattei, Josiemer (Am J Health Behav, 2016)
OBJECTIVES: We performed a qualitative assessment of Puerto Ricans’ knowledge and perceptions of cardiovascular disease (CVD), and motivations/barriers and preferences to participate in community/ clinical programs for CVD-prevention. METHODS: Four guided focus group discussions were conducted on a total of 24 Puerto Ricans, aged 40–60 years in Boston, MA. RESULTS: Participants were aware of CVD, but less knowledgeable about its prevention. They perceived it as serious, and either had CVD or knew someone who had it. They favored education and activities on nutrition, exercise, clinical advice, and social interaction, in weekly/ biweekly small-group sessions with other Latinos, led in Spanish by a familiar health professional, in a convenient community location. Age- and culture-specific program content and educational materials were preferred. A theme emerged on ‘personal or family motivations’ such as to become healthier and live longer so they would feel better and support their families, or to learn about CVD-prevention. Main barriers included family obligations, weather, safety concerns, transportation, and depressive mood. CONCLUSIONS: Culturally-tailored CVD-prevention programs for Puerto Ricans should include multiple behavioral and social approaches, and draw on intrinsic motivators while reducing barriers to help enhance efficacy and sustainability.